The Effects of Tai Chi on Healthy Aging and Quality of Life in Seniors - Szczot, Jakub; Stencel, Nicola Joanna; Krala-Szkaradowska, Magdalena; Skrzypczak, Katarzyna Oktawia; Stuczyński , Sebastian Krzysztof (Quality in Sport, 2024)
Introduction and Purpose: As the global population ages, ensuring a good quality of life for older adults becomes increasingly crucial. Tai Chi is a mind-body practice originating from ancient China that combines elements of martial arts, meditation, and focused visualization. In recent years, it has gained increasing popularity in the West, particularly due to its numerous health benefits. The purpose of this article is to review the health benefits of Tai Chi for the elderly population. Materials and Methods: A literature search was conducted using the medical databases PubMed and Google Scholar. Articles were retrieved in English, employing the keywords: „Tai Chi”, „elderly”, „ postural balance”, „ rehabilitation”, „cognition”. State of Knowledge: Tai Chi is a safe form of exercise for older adults. This practice involves slow, harmonious body movements synchronized with deep breathing and concentration. A growing body of research supports the benefits of Tai Chi as an integrative strategy in the treatment and rehabilitation of various age-related conditions. The therapeutic effects of Tai Chi for the health of seniors include improvements in balance, bone health, sleep quality, immunity, cognitive function, metabolic indicators, and cardiorespiratory fitness, as well as the alleviation of pain, symptoms of depression, stress, and anxiety. Summary: Tai Chi may support healthy aging by improving balance, fitness, and quality of life in older adults, but additional research is needed to fully understand its impact on health.